Photodimerization and photocycloaddition of 2-cyclohexenone in confined space of cation-exchanged Y zeolites - Yeoh , Kar Kheng; Yacob, Abdul Rahim; Ahmad, Farediah (Penerbit Universiti Sains Malaysia, 2004)
Zeolite Y was used in this research. The structure of FAU zeolite is cubic and built from sodalite cage connected via the double 6-membered ring. It forms a three-dimensional network of nearly spherical supercages of about 1.3 nm in diameter connected tetrahedrally to four other supercages through 0.74 nm windows. The charge-compensating cations are mobile and distributed among several types of sites.